To control site-specific skin gene expression, autocrine mimics paracrine canonical Wnt signaling and Is activated ectopically in skin disease - Kim, Dongwon; M. Zulfiquer Hossain; Nieves, Ashley; Gu, Lihong; Ratliff, Tabetha S.; Oh, Seung Mi; Park, Angela; Han, Seunghyun; Yang, Nicole B.; Qi, Ji; Taube, Janis M.; Kang, Sewon; et al. (© 2016 American Society for Investigative Pathology, 2016)
This article was published in American Journal of Pathology, [© 2016 American Society for Investigative Pathology] and the definite version is available at https://jhu.pure.elsevier.com/en/publications/to-control-site-specific-skin-gene-expression-autocrine-mimics-pa The article website is at: http://ajp.amjpathol.org/article/S0002-9440(16)00136-X/fulltext